Experimental and numerical thermo-mechanical analysis of the influence of thermoplastic slabs installation on the assessment of their fire hazard. (September 2019) - Vincent, Chloë; Corn, Stéphane; Longuet, Claire; Aprin, Laurent; Rambaud, Guillaume; Ferry, Laurent
Abstract: This work aims at determining the influence of orientation and dimensions of structural samples on the measurement of their burning properties and therefore on the assessment of fire hazard. Poly (methylmethacrylate) (PMMA) slabs are tested thanks to a new experimental setup specially designed to study the combustion of large samples exposed to medium to high radiative heat fluxes. The experimental results evidence a relation between the heat release rate (HRR) and structural phenomena such as mechanical instability, slump, collapse and material flow. The understanding of the dimensions-behavior relationship is completed by finite element simulations of the conducted experiments. The thermo-mechanical simulations consist in the sequence of a transient thermal computation up to a given heating time followed by an eigen buckling calculation, all encapsulated in a parametric study of that heating time. The evolution of the buckling critical load factor as a function of heating time allows predicting for samples of different sizes the time needed to buckle. These simulations corroborate the experimental results, namely that buckling occurs sooner for thin or large samples, which elucidates the discrepancies between the fire response assessed in vertical and horizontal sample orientations. Graphical abstract: Image 1 Highlights: The kinetics of sample slump and dripping are impaired by the PMMA slab thickness. The PMMA slab slump is largely affected by the sample surface area and has a significant impact on the burning rate. Thermo-mechanical FE simulations confirmed that the more sample is thin or large the sooner the buckling occurs.